1959
DOI: 10.1136/bjo.43.10.638
|View full text |Cite
|
Sign up to set email alerts
|

Snake Venom Conjunctivitis

Abstract: THE relative mildness of this case is thought to be of interest.Case Report A Mandinka adult male was clearing scrub in a garden near Bathurst, Gambia, when he felt a spray over the left side of his face and left eye while bending down. This had come from a snake about three feet away from him, which then disappeared; from the description it seemed to be a cobra of the species Naja (Naja nigricollis).The man immediately attended at a clinic and was examined about half an hour after the incident. He did not app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

1961
1961
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…[ 1 2 ] Ocular manifestations of snake bite reported in literature range from direct injury to the eye leading to penetrating injuries with bite marks, conjunctival and corneal lacerations, subconjunctival hemorrhage, keratomalacia, hyphema, uveitis, acute angle closure glaucoma (ACG), optic neuritis, external ophthalmoplegia, vitreous hemorrhage, and endophthalmitis resulting in blindness. [ 3 4 5 6 7 ] A thorough review of literature shows isolated case reports describing ACG following a snake bite. [ 8 9 ] We report a case series of acute ACG following snake bite, their clinical characteristics, management, and outcomes observed over 1 year in a tertiary care center in India.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 2 ] Ocular manifestations of snake bite reported in literature range from direct injury to the eye leading to penetrating injuries with bite marks, conjunctival and corneal lacerations, subconjunctival hemorrhage, keratomalacia, hyphema, uveitis, acute angle closure glaucoma (ACG), optic neuritis, external ophthalmoplegia, vitreous hemorrhage, and endophthalmitis resulting in blindness. [ 3 4 5 6 7 ] A thorough review of literature shows isolated case reports describing ACG following a snake bite. [ 8 9 ] We report a case series of acute ACG following snake bite, their clinical characteristics, management, and outcomes observed over 1 year in a tertiary care center in India.…”
Section: Introductionmentioning
confidence: 99%
“…Vitreous haemorrhage, macular infarction and central retinal artery occlusion can occur as a result of haemotoxicity [5][6][7]. Chemosis, conjunctivitis, corneal oedema and corneal ulceration as a manifestation of snake venom ophthalmia, a condition resulting from the venom ejected from spitting cobras common in Africa, has been reported [8]. Direct inoculation of venom into the eye has been known to cause globe necrosis, keratomalacia and uveitis, often ending up requiring evisceration or enucleation [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to other studies from India where neurotoxic snake bite was reported to be the most common followed by viper bite [ 4 5 ]. Various ocular manifestations of snake bite described in the literature are bilateral angle closure glaucoma, chemical injury to the eye from spitting of highly irritant snake venom [ 6 7 ], direct injury to the eye leading to penetrating injuries with bite marks, conjunctival and corneal lacerations [ 8 ]. Subconjunctival hemorrhages and hyphema due to the systemic hematotoxicity, keratomalacia due to collagenase in the snake venom causing stromal lysis, uveitis as a result of serum sickness-like response occurring due to ASV or direct toxicity of venom in penetrating injuries and endophthalmitis have also been reported [ 9 10 11 ].…”
Section: Discussionmentioning
confidence: 99%